Bahaya Merokok Pada Remaja - Tivany Ramadhani; Usna Aulia; Winda Amelia Putri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Cigarettes are generally smoked, and when lit, the tobacco inside burns and produces smoke that is inhaled by the smoker. Cigarettes contain nicotine, tar and various other chemicals, which have a bad impact on human health. Excessive smoking has been linked to a variety of serious illnesses, including heart disease, cancer, lung disease, and other health problems.